Q. 35.0( 5 Votes )

Verify the proper

Answer :

(i) () * ( + )

= * + *


= +


=


=


=


x * y + x * z =


() * () = *


=


() * ( + ) = () * () + () * ()


(ii) () * ( + )


= * ( )


=


x * y + x * z


() * () + () * ()


=


(iii) * ( + ) = () * () + () * ()


* () = +


=


=


Therefore,


L.H.S = R.H.S


(iv) ( + ) = () * () + () * ()


* + * = ( + )


+ = ( - )


= ( )


= ()


=


1 = 1


Therefore,


L.H.S = R.H.S


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Verify the properRD Sharma - Mathematics

The sum of the twRD Sharma - Mathematics

The sum of two nuRD Sharma - Mathematics

Tell which properNCERT - Mathematics Exemplar

Find the multipliNCERT - Mathematics Exemplar

What number shoulRD Sharma - Mathematics